RIVALITĂŢI CORPORATIVE ÎN TESTAREA COMPETENŢELOR PROFESIONALE - COŞERIU, Tatiana (BIBLIOPOLIS, 2020)
Today the professional competences represent the brand of infodocumentary institution. The librarian professionalism assures the quality of the activity and serves to the improving of knowledge management. The implementation of the innovative forms of competence evaluation allows the team coesion, the development of creativity and equity.